The Impact of Early Clinical Exposure on the Knowledge and Attitude of Basic Sciences Medical Students at Tabriz University of Medical Sciences - Afra Bita; Alizadeh Mahasti; Taghavi Simin; Jabbari Bayrami Hossein; Yari Javaher (Tabriz University of Medical Sciences, 2015)
Introduction: This study aimed to examine the effects of early clinical exposure to mother and child healthcare on the knowledge and attitude of Tabriz medical school basic sciences students. Methods: As a sample, 152 of the third semester students were selected, of whom 25 were randomized to the experimental group and the rest, 127 students, were considered the control group. Results: The results of the study showed that there was a significant difference between the attitudes and knowledge level of the control group who did not experience early clinical exposure and the experimental group who were given clinical exposure with regard to intervention training. Conclusion: Finally, considering the results, it could be acknowledged that training in the intervention of early clinical exposure could affect the level of students' knowledge and attitudes.